2013
DOI: 10.4028/www.scientific.net/msf.753.185
|View full text |Cite
|
Sign up to set email alerts
|

Martensite Formation and Recrystallization Behavior in 17Mn0.06C2Si3Al1Ni TRIP/TWIP Steel after Hot and Cold Rolling

Abstract: This work evaluates the evolution of the microstructure and its influence on the mechanical behavior of steel containing 17% Mn, 0.06% C, 2% Si, 3% Al, and 1% Ni after hot rolling at 1070°C, cold rolling with 44% reduction, and annealing at 700°C for different time periods. The resultant athermal, strain-induced martensite and austenite grains were analyzed by optical and scanning electron microscopy (SEM). The volume fractions of the g, e, and α’ phases of martensite were confirmed by X-ray diffraction, dilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
(45 reference statements)
1
6
0
2
Order By: Relevance
“…It was shown in earlier work that this is observed in the stress-strain curves of the material used in these experiments without HPT processing [23]. Thus, these experiments showed that the flow stress increased from ~200…”
Section: The Strain Hardening Behavior After Hptsupporting
confidence: 49%
See 2 more Smart Citations
“…It was shown in earlier work that this is observed in the stress-strain curves of the material used in these experiments without HPT processing [23]. Thus, these experiments showed that the flow stress increased from ~200…”
Section: The Strain Hardening Behavior After Hptsupporting
confidence: 49%
“…However, the transformation is expected to be complete at low values of straining at room temperature leading to an almost complete α' microstructure. It is interesting to note that a similar alloy was subjected to cold rolling and it was found that a 44% thickness reduction gave ~78% of α' phase [23] whereas a 90% thickness reduction led to ~98.5% of α'. The present results…”
Section: Stabilization Of the ε Phase By Hptmentioning
confidence: 97%
See 1 more Smart Citation
“…In order to be able to predict the deformation mechanisms of the various heat treated samples, their SFE values were estimated using the model proposed by Dumay et al [4]. The value obtained was 14.5 mJ m −2 [23,24], which indicates the occurrence of martensitic transformation as a plastic deformation mechanism, as well as mechanical twinning and dislocations slip. Dilatometric results demonstrate that the martensite phase occurs in steel samples subjected to deformation, that is strain induced mode and having a low SFE.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were first etched with nital (10%) and then with Klemm's I etchant [23,24]. For the Scanning electron microscopy (SEM) measurements, the samples were etched with Villela etchant.…”
Section: Methodsmentioning
confidence: 99%